The Evolving Treatment Landscape of AML - Sabine Blum; Ulrike Bacher; Thomas Pabst (healthbook TIMES. Oncology Hematology)
Acute myeloid leukemia (AML) is the most common type of acute leukemia in adults and is associated with poor long-term survival and a high relapse rate, mainly due to relapse and resistance to available therapies. The recent advancements in the technologies for genomic profiling, particularly next-generation sequencing (NGS), have enabled the identification of recurrent and novel genetic mutations implicated in the pathogenesis of AML. This resulted in refined risk stratification and the development of more effective targeted therapies, like FMS-like tyrosine kinase 3 (FLT3) and isocitrate dehydrogenase 1/2 (IDH1/2) inhibitors. Over the last years, B-cell lymphoma-2 (BCL-2), a key regulator of the intrinsic apoptotic pathway, has also emerged as a relevant target for therapy for many diseases including AML, and promising results were reported with the use of BCL-2 inhibitors. This article will present an overview of some recent breakthroughs in the field of AML, with a focus on the latest drug approvals in AML. The assessment of minimal/measurable residual disease (MRD) and its role in treatment decision-making will also be briefly discussed.